2020
DOI: 10.23736/s0022-4707.20.10384-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of four weeks of plyometric training on reactive strength index and leg stiffness is sport dependent

Abstract: BACKGROUND: Plyometric exercises are often used to develop lower limb strength and performance-related biomechanics such as leg stiffness. However, the effectiveness of plyometric training may depend on participants' own training and performance demands. The purpose of this study was to examine the effect of plyometric training on reactive strength index (RSI) and leg stiffness (Kleg) on young athletes of different sports. METHODS: Forty eight female athletes (25 Taekwondo (TKD) & 23 rhythmic gymnastics (RG), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
0
19
1
Order By: Relevance
“…RSI is an indicator of how efficiently athletes perform the SSC. Although plyometric training has been shown to significantly improve the efficiency of SSC utilization (Jeffreys et al, 2019;Dallas et al, 2020), it is interesting to note that the BP group exhibited a greater increase in RSI. A potential reason could be that balance training enhanced the body control of players and finally reduced the time spent on the landing during jumps.…”
Section: Discussionmentioning
confidence: 96%
“…RSI is an indicator of how efficiently athletes perform the SSC. Although plyometric training has been shown to significantly improve the efficiency of SSC utilization (Jeffreys et al, 2019;Dallas et al, 2020), it is interesting to note that the BP group exhibited a greater increase in RSI. A potential reason could be that balance training enhanced the body control of players and finally reduced the time spent on the landing during jumps.…”
Section: Discussionmentioning
confidence: 96%
“…The observed improvements in reactive strength indices were an expected finding of this SRMA. Surprisingly, however, this outcome is in contradiction to the absence of an effect of JT on stiffness measures, as reactive strength indices are supposedly proxies of neuromuscular stiffness (Dallas et al, 2020;Flanagan & Comyns, 2008;García-Pinillos et al, 2020b;Li, Newton, et al, 2019a;Markovic & Mikulic, 2010). This finding may be related to the limited number of studies which included different measures of stiffness (five vs. eight studies for stiffness and reactive strength, respectively), and the variety of methods and indices used.…”
Section: Reactive Strength Performancementioning
confidence: 93%
“…Other studies also showed significant improvements in the jumping performance of dancers (Wang et al, 2010;Komeroski et al, 2016;Tsanaka et al, 2017;Escobar-Alvarez et al, 2019;Stošić et al, 2020) and rhythmic gymnasts (Piazza et al, 2014;Dobrijević et al, 2018;Dallas et al, 2020) as a result of training interventions, and the improvements in jumping performance are consistent with previous findings in ballet dancers (Escobar-Alvarez et al, 2019;Alvarez et al, 2020) and in other sports disciplines (Jimenez-Reyes et al, 2016, Jiménez-Reyes et al, 2019. We suggest an exercise prescription based on the individual needs and the physical demands of ballet, jazz, and contemporary dancers as referred to in previous studies (Alvarez et al, 2020;Dowse et al, 2020).…”
Section: Almost Certainlymentioning
confidence: 91%